Republic of Tajikistan : Fifth Review Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criterion; Staff Report; and Press Release on the Executive Board Consideration. (IMF Staff Country Reports; Country Report ;, 2005)
This paper discusses Tajikistan's Fifth Review Under the Poverty Reduction and Growth Facility (PRGF) and Request for Waiver of Performance Criterion. The macroeconomic outcome in the first quarter of 2005 was satisfactory, but the deteriorating external environment will make it harder to achieve some of the program's original targets. Expenditure delays and strong nontax revenues resulted in a significant fiscal surplus in the first quarter of 2005. The fiscal outlook for the remainder of 2005 looks less favorable owing to lower-than-projected commodity prices.